Piezoelectric laminate and piezoelectric element

JP7630121B2Active Publication Date: 2025-02-17DAI NIPPON PRINTING CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2018223972
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2018-11-29
Publication Date
2025-02-17
Estimated Expiration
2038-11-29

AI Technical Summary

Technical Problem

The c-axis orientation of aluminum nitride layers formed on metal substrates is deteriorated, leading to reduced piezoelectricity, and controlling residual stress is challenging due to the high thermal expansion coefficient mismatch between metal substrates and aluminum nitride.

Method used

A piezoelectric laminate is developed with a metal substrate having a thermal expansion coefficient of 4-18 ppm/K and a buffer layer, such as Ni, between the metal substrate and aluminum nitride layer to improve c-axis orientation and reduce thermal stress.

Benefits of technology

The c-axis orientation of aluminum nitride is enhanced, improving piezoelectricity, and the laminate can be made flexible for applications in severe environments and curved surfaces.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000010_0000
    Figure 00000010_0000
  • Figure 00000011_0000
    Figure 00000011_0000
  • Figure 00000011_0001
    Figure 00000011_0001
Patent Text Reader

Abstract

To improve c-axis orientation of aluminum nitride provided on a metal substrate to improve piezoelectricity.SOLUTION: The piezoelectric laminate has a metal substrate having a first surface and a second surface, a buffer layer provided on the first surface of the metal substrate, and an aluminum nitride layer, provided on the buffer layer, having piezoelectricity.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0004]

[0001] One embodiment of the present disclosure relates to a piezoelectric laminate and a method for manufacturing the same.

Background Art

[0002] It is known to form a piezoelectric element by providing aluminum nitride with uniaxial orientation along the c-axis on a silicon substrate or a glass substrate. Further, since the piezoelectricity increases as the c-axis orientation of aluminum nitride becomes higher, methods for enhancing the c-axis orientation of aluminum nitride have been studied. For example, Patent Documents 1 and 2 disclose that the c-axis orientation can be improved by providing a buffer layer such as tungsten or platinum between a silicon substrate or a glass substrate and aluminum nitride.

Prior Art Documents

Patent Documents

[0003]

Patent Document 1

Patent Document 2

Summary of the Invention

Problems to be Solved by the Invention

[0004] When forming an aluminum nitride layer on a substrate, the c-axis orientation of the aluminum nitride layer is greatly affected by the surface of the substrate or the surface of the buffer layer. When forming aluminum nitride on a metal substrate instead of a silicon substrate or a glass substrate, there is a problem that the c-axis orientation decreases and the piezoelectricity decreases. Further, when it is desired to control the residual stress of the aluminum nitride layer, if a metal substrate having a thermal expansion coefficient several times that of the thermal expansion coefficient of aluminum nitride of about 4.7 ppm / K is used, the thermal stress becomes large, and it is difficult to make the residual stress, which is the sum of the thermal stress and the true stress, near zero.

[0005] One object of the present disclosure is to improve the c-axis orientation of aluminum nitride provided on a metal substrate and improve the piezoelectricity.

Means for Solving the Problems

[0006] A piezoelectric laminate according to one embodiment of the present disclosure comprises a metal substrate having a first surface and a second surface, a buffer layer provided on the first surface of the metal substrate, and a piezoelectric aluminum nitride layer provided on the buffer layer.

[0007] In the piezoelectric laminate described above, the metal substrate has a thermal expansion coefficient of 4 ppm / K to 18 ppm / K in a temperature range of 30°C to 300°C.

[0008] In the piezoelectric laminate described above, the buffer layer contains Ni.

[0009] In the piezoelectric laminate described above, the buffer layer is Al, Mo, or Ru, or an alloy thereof, or a nitride thereof.

[0010] In the piezoelectric laminate described above, the buffer layer is made of Ti, W, or Pt, or an alloy thereof, or a nitride thereof.

[0011] In the piezoelectric laminate described above, the buffer layer is made of Ni, Ti, Al, W, Mo, Ru, or Pt, or an alloy thereof, or a nitride thereof.

[0012] In the piezoelectric laminate described above, the thickness of the metal substrate is 10 μm or more and 1000 μm or less.

[0013] In the piezoelectric laminate described above, the thickness of the buffer layer is between 10 nm and 200 nm.

[0014] In the piezoelectric laminate described above, the metal substrate is Fe, Ni, Ti, Al, Mo, or W.

[0015] In the piezoelectric laminate described above, the metal substrate is an Fe-based alloy, a Ni-based alloy, an Al-based alloy, a Mo-based alloy, or a W-based alloy.

[0016] In the above piezoelectric laminate, the Fe-based alloy is SUS304, SUS316, or SUS430.

[0017] In the piezoelectric laminate described above, the Ni-based alloy is 42Alloy, Invar, or Kovar.

[0018] A piezoelectric laminate according to one embodiment of this disclosure is flexible.

[0019] A piezoelectric element according to one embodiment of the present disclosure comprises a piezoelectric laminate according to one embodiment of the present disclosure and a first electrode provided on an aluminum nitride layer, wherein the metal substrate functions as a second electrode. [Effects of the Invention]

[0020] According to this disclosure, the piezoelectric properties can be improved by improving the c-axis orientation of aluminum nitride provided on a metal substrate. [Brief explanation of the drawing]

[0021] [Figure 1] This is a cross-sectional view of a piezoelectric laminate according to one embodiment of the present disclosure. [Figure 2] (A) A cross-sectional view showing a method for manufacturing a piezoelectric laminate according to one embodiment of the present disclosure. (B) A cross-sectional view showing a method for manufacturing a piezoelectric laminate according to one embodiment of the present disclosure. (C) A cross-sectional view showing a method for manufacturing a piezoelectric laminate according to one embodiment of the present disclosure. [Figure 3] This is a cross-sectional view of a piezoelectric element using a piezoelectric laminate according to one embodiment of the present disclosure. [Figure 4] This is a cross-sectional view of a piezoelectric element using a piezoelectric laminate according to one embodiment of the present disclosure. [Figure 5] Figure 5(A) shows the shape of an evaluation sample in which a 3 μm thick aluminum nitride layer is provided on a 50 μm thick 42 Alloy foil via a 100 nm thick Ni / 50 μm thick layer. Figure 5(B) shows the piezoelectric beam shown in Figure 5(A) fixed to a glass jig with wiring so that the effective length of the beam is 6.5 mm. [Figure 6] FIG. 6(A) is an overall photograph of a 3-μm-thick aluminum nitride layer provided via a 100-nm-thick Ni on a 50-μm-thick 42Alloy foil. FIG. 6(B) shows the surface properties of the aluminum nitride layer photographed by a field emission electron microscope. [FIG. 7] FIG. 4 is a 2θ-θ diagram in the X-ray crystallographic analysis of a 3-μm-thick aluminum nitride layer provided via a 100-nm-thick Ni on a 50-μm-thick 42Alloy foil. [FIG. 8] FIG. 8 shows the results of the X-ray rocking curve measurement of the aluminum nitride layer shown in FIG. 7. [FIG. 9] FIG. 12 is a diagram showing the applied voltage frequency-piezoelectric beam tip displacement characteristics by a piezoelectric beam. [FIG. 10] FIG. 16 is a diagram showing the applied voltage peak-to-peak value-piezoelectric beam tip displacement characteristics by a piezoelectric beam. [MODE FOR CARRYING OUT THE INVENTION]

[0022] Hereinafter, the contents of the embodiments of the present invention will be described with reference to the drawings and the like. However, the present invention includes many different aspects and is not to be construed as limited to the contents of the embodiments illustrated below. The drawings may schematically represent the width, thickness, shape, etc. of each part compared to the actual aspect for the sake of clearer explanation, but this is merely an example and does not limit the contents of the present invention. Also, in this specification, when an element described in one drawing and an element described in another drawing are in the same or corresponding relationship, the same reference numeral (or a reference numeral with A, B, etc. appended after the number described as the reference numeral) may be given, and repeated explanations may be omitted as appropriate. Furthermore, the letters "first" and "second" appended to each element are for convenience of distinguishing each element and have no further meaning unless otherwise specified.

[0023] (First Embodiment) In this embodiment, the structure and manufacturing method of a piezoelectric laminate 100 according to an embodiment of the present disclosure will be described with reference to FIGS. 1 to 3.

[0024] [Structure of Piezoelectric Laminate] Figure 1 is a cross-sectional view illustrating the structure of a piezoelectric laminate 100 according to one embodiment of the present disclosure. As shown in Figure 1, the piezoelectric laminate 100 includes a metal substrate 101 having a first surface 101A and a second surface 101B, a buffer layer 102 provided on the first surface 101A of the metal substrate 101, and an aluminum nitride layer 103 provided on the buffer layer 102 and having piezoelectric properties in the thickness direction.

[0025] When depositing an aluminum nitride layer on a substrate, the c-axis orientation of the aluminum nitride layer is greatly influenced by the surface of the substrate or the surface of the buffer layer.

[0026] Generally, substrates are heated to around 400°C during film deposition. Therefore, silicon or glass substrates, which are less prone to warping or deformation at high temperatures, have been used. Because the difference between the thermal expansion coefficients of silicon or glass substrates and aluminum nitride is small, problems such as substrate deformation are unlikely even when these substrates are subjected to high temperatures. For this reason, metal substrates have not traditionally been used to form piezoelectric laminates.

[0027] Furthermore, in order to improve the c-axis orientation of the aluminum nitride layer, various materials have been considered for use as a buffer layer between the silicon substrate or glass substrate and the aluminum nitride layer. However, even when a nickel layer is deposited on a silicon substrate or glass substrate and then an aluminum nitride layer is deposited, the c-axis orientation of the aluminum nitride layer decreases, which is a problem.

[0028] In recent years, piezoelectric materials have been desired for use in piezoelectric laminates, particularly in harsh environments where piezoelectric combustion pressure sensors and vibration power generation elements are placed, subject to temperatures exceeding several hundred degrees Celsius and constant shocks. Such harsh environments cannot be withstood by lead zirconate titanate-based ceramics in bulk sintered form, nor by piezoelectric MEMS using lead zirconate titanate thin films and silicon substrates. As a piezoelectric component that can withstand such harsh environments, a piezoelectric laminate combining a piezoelectric thin film made of aluminum nitride, which practically has no Curie point, with a metal substrate that does not undergo brittle fracture, is conceivable. In this case, if the metal substrate is thinned to about 100 μm or less, the flexibility of the piezoelectric laminate desired in the field of flexible electronics, where installation on curved objects such as the human body or structures can be achieved. However, when using a metal substrate instead of a silicon or glass substrate, a problem arises in that the c-axis orientation decreases, and the piezoelectric properties decrease when an aluminum nitride layer is deposited on the metal substrate.

[0029] For the reasons stated above, it was desirable to improve the piezoelectric properties of the aluminum nitride layer, even when using a metal substrate.

[0030] As a result of diligent research, the inventors have found that forming a buffer layer on a metal substrate improves the c-axis orientation of the aluminum nitride layer. Consequently, they have found that the piezoelectric properties of the piezoelectric laminate are improved.

[0031] Therefore, in the piezoelectric laminate 100 according to one embodiment of this disclosure, a buffer layer 102 having a buffering function is provided between the metal substrate 101 and the aluminum nitride layer 103. In one embodiment of this disclosure, nickel was selected as the buffer layer 102. Furthermore, the metal substrate 101 is used such that the difference between the thermal expansion coefficient of the metal substrate 101 and the thermal expansion coefficient of the aluminum nitride layer is small. The configuration of the piezoelectric laminate 100 according to one embodiment of this disclosure will be described in detail below.

[0032] For example, Fe, Ni, Ti, Al, Mo, or W can be used as the metal substrate 101. Alternatively, Fe-based alloys, Ni-based alloys, Al-based alloys, Mo-based alloys, or W-based alloys can be used as the metal substrate 101. Furthermore, for Fe-based alloys, SUS304, SUS316, or SUS430 can be used. For Ni-based alloys, 42-Alloy, Invar, or Kovar can be used.

[0033] Below are examples of the compositions and thermal expansion coefficients of major alloy substrates: SUS304, SUS430, 42Alloy, and Kovar.

[0034] SUS304 is an austenitic stainless steel, an alloy of chromium and nickel. The main components of SUS304 are Fe bal, Ni 10%, Cr 18%, Mn 2%, Si 1% or less, and C 0.08% or less. The thermal expansion coefficient of SUS304 between 30°C and 300°C is approximately 18 ppm / K.

[0035] SUS430 is a ferritic stainless steel and a chromium alloy. The main components of SUS430 are Fe bal, Al 0.2%, Cr 12.5%, Mn 1% or less, Si 1% or less, and C 0.08% or less. The thermal expansion coefficient of SUS430 between 30°C and 300°C is approximately 13 ppm / K.

[0036] 42Alloy is an iron-nickel alloy. The main components of 42Alloy are, for example, Fe bal, Ni 42%, Mn 0.53%, Co 0.37%, and Si 0.06%. The thermal expansion coefficient of 42Alloy between 30°C and 300°C is approximately 4 ppm / K. Iron-nickel alloys like 42Alloy are preferred because their thermal expansion coefficient is low due to the counteracting effect of lattice expansion caused by heat and lattice narrowing due to the magnetic properties within the alloy.

[0037] Kovar is an alloy of iron, nickel, and cobalt. The main components of Kovar are, for example, Fe bal, Ni 29%, Mn 0.3%, Co 17%, and Si 0.02%. The thermal expansion coefficient of Kovar between 30°C and 300°C is 5 ppm / K.

[0038] The composition ratio of the metal substrate 101 described above is just one example and is not limited to the values ​​shown.

[0039] Furthermore, it is preferable that the metal substrate 101 has a thermal expansion coefficient of 4 ppm / K or more and 18 ppm / K or less at temperatures between 30°C and 300°C. In other words, it is preferable that the absolute value of the difference between the thermal expansion coefficient of the metal substrate 101 and the thermal expansion coefficient of the aluminum nitride layer 103 is 14 ppm / K or less at temperatures between 30°C and 300°C. If the absolute value of the difference between the thermal expansion coefficient of the metal substrate 101 and the thermal expansion coefficient of the aluminum nitride layer 103 exceeds 14 ppm / K at temperatures between 30°C and 300°C, it may not be possible to achieve a stress-free state solely by controlling residual stress by adjusting the film deposition conditions of the aluminum nitride, and the piezoelectric laminate 100 may deform. Note that the material that can be used as the metal substrate 101 is not limited to the material listed above, and other materials may be used as long as they satisfy the condition that the absolute value of the difference between the thermal expansion coefficient of the metal substrate 101 and the thermal expansion coefficient of the aluminum nitride layer 103 is 14 ppm / K or less at temperatures between 30°C and 300°C.

[0040] The thickness of the metal substrate 101 is preferably between 10 μm and 1000 μm. The method for forming the metal substrate 101 will be described in detail later. By making the thickness of the metal substrate 101 about 100 μm or less, the metal substrate 101 can be made flexible, so that a bendable piezoelectric laminate 100 can be formed. Because the piezoelectric laminate 100 is flexible, the piezoelectric laminate 100 can be attached to a structure having a curved surface.

[0041] The buffer layer 102 is provided between the metal substrate 101 and the aluminum nitride layer 103. While the buffer layer may be an alloy or metal nitride as long as its composition and surface properties are uniform, a pure metal is preferable due to its ease of control. When selecting the buffer layer 102, lattice matching should be considered. For example, nickel is preferred as the buffer layer material because the hcp(001) plane of aluminum nitride and the fcc(111) plane of nickel are lattice-matched. The buffer layer 102 is provided by sputtering with a film thickness of 10 nm to 200 nm. In this embodiment, the case where nickel is used as the buffer layer 102 is described, but it is not limited to nickel; Ti, Al, W, Mo, Ru, or Pt, or alloys or nitrides thereof, may also be used.

[0042] The aluminum nitride layer 103 is provided on the buffer layer 102 by reactive sputtering. The film thickness can be made as thick as required for the application device, but generally, cracks tend to occur when the thickness exceeds several micrometers. In one embodiment of this disclosure, the aluminum nitride layer 103 has a film thickness in the range of 1 μm to 10 μm and has a high c-axis orientation.

[0043] In one embodiment of this disclosure, a buffer layer 102 made of, for example, nickel is provided between the metal substrate 101 and the aluminum nitride layer 103, thereby mitigating lattice mismatch between the metal substrate 101 and the aluminum nitride layer 103. Furthermore, by setting the thermal expansion coefficient of the metal substrate 101 to 4 ppm / K to 18 ppm / K at temperatures between 30°C and 300°C, the difference with the thermal expansion coefficient of the aluminum nitride layer 103 can be reduced. This makes it possible to suppress deformation of the metal substrate 101 during the deposition of the aluminum nitride layer 103.

[0044] [Manufacturing method for piezoelectric laminates] A method for manufacturing a piezoelectric laminate 100 according to one embodiment of this disclosure will be described with reference to Figures 2(A) to 2(C).

[0045] Figure 2(A) is a cross-sectional view of the metal substrate 101. SUS304, SUS430, 42Alloy, and Kovar are used as the metal substrate 101.

[0046] The metal substrate 101 has a thickness of 10 μm or more and 500 μm or less, and has a clean and flattened surface.

[0047] Figure 2(B) illustrates the process of forming a buffer layer 102 on a metal substrate 101. The buffer layer 102 can be formed using methods such as vapor deposition, plating, or sputtering, and the method of formation is not particularly limited. In this embodiment, for example, a nickel layer is formed as the buffer layer 102 using an RF magnetron sputtering apparatus. The thickness of the buffer layer 102 is formed to be between 10 nm and 200 nm. Furthermore, in order to improve the c-axis orientation of the aluminum nitride layer 103 that is formed later, it is preferable that the surface of the buffer layer 102 has high flatness.

[0048] Figure 2(C) illustrates the process of depositing an aluminum nitride layer 103 on the buffer layer 102. The aluminum nitride layer 103 is deposited to a thickness of 1 μm to 10 μm using methods such as hydride vapor deposition (HVPE), metal-organic vapor deposition (MOCVD), pulsed laser deposition (PLD), DC sputtering, pulsed DC sputtering, and RF sputtering. In this embodiment, the case in which the aluminum nitride layer 103 is deposited using reactive magnetron sputtering is described. Reactive sputtering is preferable because it allows for lower deposition temperatures and enables the deposition of a high-quality aluminum nitride layer 103 over a large area.

[0049] The residual stress applied to the aluminum nitride layer 103 consists of thermal stress and intrinsic stress. By controlling the film deposition conditions, the thermal stress applied to the aluminum nitride layer 103 can be offset by the intrinsic stress. In addition, in this embodiment, a metal substrate 101 is used in which the difference between the thermal expansion coefficient of the metal substrate 101 and the thermal expansion coefficient of the aluminum nitride layer 103 is small. Therefore, deformation of the metal substrate 101 due to heat can be suppressed, making it easier to control the stress of the aluminum nitride layer 103.

[0050] Through the above process, a piezoelectric laminate 100 can be formed in which a buffer layer 102 is provided between the metal substrate 101 and the aluminum nitride layer 103.

[0051] (Second Embodiment) In this embodiment, the configuration of a piezoelectric element 110 using a piezoelectric laminate 100 according to one embodiment of the present disclosure will be described with reference to Figures 3 and 4.

[0052] As shown in Figure 3, the piezoelectric element 110 includes a piezoelectric laminate 100, an electrode 104 provided on the second surface 101B of the metal substrate 101, and an electrode 105 provided on the first surface 101A of the aluminum nitride layer 103. In this embodiment, the piezoelectric element also functions as an electrode on the metal substrate 101. Therefore, the piezoelectric element 110 may function with the piezoelectric laminate 100 and the electrode 105 on the first surface 101A of the aluminum nitride layer 103 as one electrode, and the metal substrate 101 as the other electrode.

[0053] Electrodes 104 and 105 are formed using, for example, aluminum, tungsten, molybdenum, titanium platinum, chromium gold, etc.

[0054] As shown in Figure 4, the piezoelectric element 110A includes a piezoelectric laminate 100A, an electrode 104, and an electrode 105. The piezoelectric element 110A includes a buffer layer 102 provided on the first surface 101A of the metal substrate 101, an aluminum nitride layer 103, an electrode 105, a buffer layer 102A provided on the second surface 101B of the metal substrate 101, an aluminum nitride layer 103A, and an electrode 104.

[0055] Considering the stress applied to the piezoelectric laminate 100A, it is preferable that the film thicknesses of the buffer layer 102 and the buffer layer 102A are approximately the same, and that the film thicknesses of the aluminum nitride layer 103 and the aluminum nitride layer 103A are approximately the same.

[0056] The piezoelectric element 110 according to this disclosure can be made flexible by thinning the metal substrate. Therefore, the piezoelectric element 110 can be attached to a curved structure and used as a sensor component for a wearable device. Furthermore, the piezoelectric element 110 according to one embodiment of this disclosure can be used as a piezoelectric component for a vibration power generation element and can be used as a power supply element by combining it with a power management circuit. Such a power supply element is also called an energy harvesting element and can be used as a power source for terminal elements of sensor networks for tire pressure monitoring systems and infrastructure life diagnosis systems such as railways and highways, which are installed in locations where wired power supply or battery operation is difficult. In addition, the piezoelectric element 110 can also be applied to piezoelectric sensors and actuators. Specifically, these include microphones, speakers, strain sensors, fingerprint sensors, acoustic emission sensors, photoacoustic sensors, and vibration sensors. [Examples]

[0057] In this embodiment, we will describe the results of comparing the full width at half maximum of the rocking curve when an aluminum nitride layer is formed on a metal substrate and when an aluminum nitride layer is formed on a metal substrate via a nickel layer, and the evaluation performed using a piezoelectric beam to confirm the piezoelectric properties of the film.

[0058] [Example 1] In Example 1, a 42Alloy substrate with a thickness of 500 μm and a clean and flat surface was used as the metal substrate 101.

[0059] Next, a buffer layer 102 was deposited on the metal substrate 101 using nickel with an RF magnetron sputtering system. The deposition conditions for the buffer layer 102 were as follows: nickel was used as the target, and a thickness of 100 nm was deposited at room temperature.

[0060] Next, an aluminum nitride layer 103 was deposited on the buffer layer 102 using a reactive magnetron sputtering apparatus. The thickness of the deposited film was 1 μm.

[0061] Through the above steps, Example 1 was fabricated, in which an aluminum nitride layer 103 was provided on a metal substrate 101 via a buffer layer 102.

[0062] [Comparative Example 1] Comparative Example 1 was conducted under the same conditions as in Example 1, except that a buffer layer 102 was not formed on the metal substrate 101, and an aluminum nitride layer 103 was formed on the metal substrate 101.

[0063] [Example 2] In Example 2, all conditions were the same as in Example 1 except that SUS304 was used instead of 42Alloy as the metal substrate 101. In Example 2, a buffer layer 102 was formed on the metal substrate 101 using nickel, and an aluminum nitride layer 103 was formed on the buffer layer 102.

[0064] [Comparative Example 2] Comparative Example 2 was conducted under the same conditions as in Example 2, except that a buffer layer 102 was not formed on the metal substrate 101, and an aluminum nitride layer 103 was formed on the metal substrate 101.

[0065] Next, the aluminum nitride layer 103 of Examples 1 and 2 and Comparative Examples 1 and 2 was measured using an XRD apparatus (BRUKER D8 ADVANCE). Table 1 shows the XRD measurement results.

[0066] [Table 1]

[0067] As shown in Table 1, compared to Comparative Examples 1 and 2, in which the aluminum nitride layer 103 was formed on the metal substrate 101 via a nickel buffer layer 102, Examples 1 and 2 showed a smaller full width at half maximum of the rocking curve.

[0068] [Example 3] To verify whether the embodiments described herein can be applied to thin metal foils, an aluminum nitride layer was formed on a 50 μm thick 42 Alloy foil metal substrate 101, and the crystal orientation and piezoelectric properties using a piezoelectric beam were evaluated. In Example 3, based on Example 1, all conditions were the same except that the metal substrate 101 was a 50 μm thick 42 Alloy foil, and a 3 μm thick aluminum nitride layer 103 was formed on the metal substrate 101 via a 100 nm thick Ni buffer layer 102.

[0069] Figure 5(A) shows the shape of an evaluation sample in which a 3 μm thick aluminum nitride layer is provided on a 50 μm thick 42 Alloy foil via a 100 nm thick Ni layer. In Figure 5(A), the 42 Alloy foil is shown as the metal substrate 211, the Ni layer as the buffer layer 212, and the aluminum nitride layer 213 and layer 214. Layer 214 consists of a 200 nm thick gold layer provided on a 15 nm thick titanium layer via a 100 nm thick nickel layer. The evaluation sample was processed into a piezoelectric beam shape with a length L10 mm and a width W1 mm ​​by dicing. In Figure 5(A), D1 is the lingitudinal direction and D2 is the width direction. The width direction corresponds to the rolling direction (RD) during the production of the 42 Alloy foil, and the lingitudinal direction corresponds to the width direction (TD: transverse direction) of the 42 Alloy foil. Figure 5(B) shows the piezoelectric beam shown in Figure 5(A) fixed to a glass jig with wiring such that the effective length of the beam is 6.5 mm. In Figure 5(B), L1 indicates the effective length of the beam. A flexible flat wire 222 is also provided on the glass jig 221. Here, the effective length of the beam refers to the distance from the end of the glass jig 221 to the position where the laser is irradiated.

[0070] Figure 6(A) shows an overall photograph of a 3 μm thick aluminum nitride layer 213 formed on a 50 μm thick 42 Alloy foil via a 100 nm thick Ni layer. Figure 6(B) shows the surface properties of the aluminum nitride layer as captured by a field emission electron microscope. As shown in Figure 6(B), densely packed crystals with a particle size of approximately 50 nm to 200 nm in diameter were observed.

[0071] Figure 7 shows the 2θ-θ diagram from the X-ray crystal analysis of a 3μm thick aluminum nitride layer, which is provided on a 50μm thick 42 Alloy foil via a 100nm thick Ni layer. As shown in Figure 7, the aluminum nitride in this embodiment exhibits a high orientation of the c axis (AlN(002)). Also in Figure 7, the Electrode metal is the peak of the upper electrode formed for piezoelectric property measurement. Figure 8 shows the results of the X-ray rocking curve measurement of the aluminum nitride layer shown in Figure 7. The full width at half maximum measured in the longitudinal direction of the beam, which is related to the function of the piezoelectric beam, was 5.00 deg.

[0072] Using the piezoelectric beam fixing jig shown in Figure 5(B), a sinusoidal voltage was applied between the upper and lower electrodes to induce piezoelectric vibration. The tip displacement of the piezoelectric beam was measured using a laser Doppler vibrometer and a digital lock-in amplifier.

[0073] Figure 9 shows the applied voltage frequency-to-piezoelectric beam tip displacement characteristics. The peak applied voltage values ​​were set to 5 and 10 Vpp. Figure 10 shows the applied voltage peak value-to-piezoelectric beam tip displacement characteristics. The applied voltage was set to 400 Hz. This piezoelectric beam evaluation confirmed that the aluminum nitride layer in Example 2 possesses piezoelectric properties. Furthermore, from these results, it can be easily inferred that the aluminum nitride layers in Examples 1 and 2 also possess piezoelectric properties on a substrate with a thickness of 500 μm.

[0074] The above results demonstrate that when forming an aluminum nitride layer 103 on a metal substrate 101, providing a nickel buffer layer 102 between them improves the c-axis orientation of the aluminum nitride layer 103. Furthermore, it was confirmed that the aluminum nitride layer according to this embodiment possesses piezoelectric properties. [Explanation of Symbols]

[0075] 101: Metal substrate, 101A: First surface, 101B: Second surface, 102: Buffer layer, 102A: Buffer layer, 103: Aluminum nitride layer, 103A: Aluminum nitride layer, 104: Electrode, 105: Electrode, 110: Piezoelectric element, 110A: Piezoelectric element, 211: Metal substrate, 212: Buffer layer, 213: Aluminum nitride layer, 214: Layer, 221: Glass jig, 222: Flexible flat wire

Claims

1. a metal substrate having a first surface and a second surface; a buffer layer provided on the first surface of the metal substrate; a piezoelectric laminate having an aluminum nitride layer provided on the buffer layer and having piezoelectric properties.

2. 2. The piezoelectric stack according to claim 1, wherein the metal substrate has a thermal expansion coefficient of 4 ppm / K or more and 18 ppm / K or less in a temperature range of 30°C or more and 300°C or less.

3. 3. The piezoelectric stack according to claim 1, wherein the buffer layer comprises Ni.

4. 3. The piezoelectric stack according to claim 1, wherein the buffer layer is made of Al, Mo, or Ru, or an alloy or nitride thereof.

5. 3. The piezoelectric stack according to claim 1, wherein the buffer layer is made of Ti, W, or Pt, or an alloy or nitride thereof.

6. 3. The piezoelectric stack according to claim 1, wherein the buffer layer is made of Ni, Ti, Al, W, Mo, Ru, or Pt, or an alloy or nitride thereof.

7. 7. The piezoelectric stack according to claim 1, wherein the metal substrate has a thickness of 10 μm or more and 1000 μm or less.

8. 8. The piezoelectric stack according to claim 1, wherein the buffer layer has a thickness of 10 nm or more and 200 nm or less.

9. 9. The piezoelectric stack according to claim 1, wherein the metal substrate is made of Fe, Ni, Ti, Al, Mo, or W.

10. 9. The piezoelectric stack according to claim 1, wherein the metal substrate is an Fe-based alloy, an Ni-based alloy, an Al-based alloy, an Mo-based alloy, or a W-based alloy.

11. 11. The piezoelectric stack according to claim 10, wherein the Fe-based alloy is SUS304, SUS316, or SUS430.

12. 12. The piezoelectric stack of claim 11, wherein the Ni-based alloy is 42Alloy, Invar, or Kovar.

13. The piezoelectric laminate according to any one of claims 1 to 12 has flexibility.

14. The piezoelectric laminate according to any one of claims 1 to 13; a first electrode provided on the aluminum nitride layer, The metal substrate functions as a second electrode.